The Correlation Of The Application Of Nutritional Conscious Family (KADARZI) Towards Toddlers Nutrition Status (INCH : Journal of Infant and Child Healthcare, 2022)
Nutrition problems are easily found in Indonesia, especially in children under five who are vulnerable to nutrition, malnutrition can impact to growth and development failure, increase mortality and morbidity and trauma in the ageprone nutrition group, namely toddlers. In Kampar Regency out of 25,914 toddlers who were weighed 2.4% were experiencing severe malnutrition and 12.9% were suffering from malnutrition, 21.7% were short. The aimed of this study was to determine the correlation between the application of nutrition conscious families (KADARZI) to the toddlers nutritional status. This research is descriptive analytic type and Cross Sectional design. Chi Square Test results with a degree of confidence of 95% showed that there was a significant correlation between the Application of Nutrition Conscious Families (KADARZI) to the Nutritional Status of Toddlers of BB/U with p value = 0.001 (p value